Flutter instability analysis of bridge decks using the step-by-step method - Khang, Nguyen Van; An, Tran Ngoc (Vietnam Journal of Mechanics, 2014)
The branch switch characteristics of coupled flutter are clarified by use of Step-by-Step flutter analysis. In the case of typically coupled flutter instability, the branch switch characteristic from torsional branch to heaving branch is observed. In this paper, a revised step-by-step analysis method is proposed and a calculating program using MATLAB is built. Finally, the flutter behavior of the Cao Lanh Bridge, which is the long bridge in Vietnam, is studied from the point of view of flutter in two-degrees of freedom, namely torsional and heaving motion.